Pittsburgh International Airport : battling turbulence in the airline industry - Land, Hunter M. (SAGE Knowledge. Cases., 2017)
Opened in 1992, the Pittsburgh International Airport midfield terminal complex was designed and built for the hub operations of USAir. Fifteen years and two bankruptcies later, US Airways has reduced what was its largest hub to a focus city with only 68 daily flights. As the airport sits half abandoned, the Allegheny Country Airport Authority is working against an industry in turmoil to rebuild service at the airport.